Hospital Patients’ Expectations on the Use of Modern Technologies by Medical Personnel - Alqahtani , Qainan Ali Jabhan; ALAsmari, Mohammed Ahmed; Al-Rashidi, Saad Daghman; AlMowalled , Sara Ahmed; Zainy , Arwa Abdullah; alkhaibari, Tahani saleh; Aldosari, Abdullah Deheem; alotaibi , Brican fahad; Alghamdi, Ohud G. D.; Albalawi , Bassam Eid; ALJOHANI, SAFWAN AHMED HUSSAIN (Journal of Ecohumanism, 2024)
Background: The integration of innovative technologies in nursing care, such as emotional robots, incident detection systems, and digital communication tools, has gained momentum. These advancements aim to enhance patient care and alleviate workforce shortages. However, their potential to address patient needs effectively, while ensuring meaningful human interaction, remains uncertain. Patients’ perspectives are crucial in understanding the benefits and challenges of these technologies. Methods: This study was conducted using semi-structured, in-depth interviews with hospitalized patients to explore their perceptions of emerging nursing technologies. Participants were presented with eight innovative devices through videos and text descriptions. The interviews, guided by open-ended questions, aimed to capture attitudes toward the impact of these technologies on patient care and nursing practices. Data were analyzed using a content analysis framework, combining deductive and inductive approaches. Results: Seventeen patients participated, sharing mixed perceptions of the technologies. Positive outcomes included improved autonomy, enhanced well-being, and better safety. However, concerns were raised about diminished human interaction, privacy risks, and the potential over-reliance on devices. Patients emphasized the importance of training, reliability, and alignment with core caregiving principles to ensure successful integration. Perceptions varied based on age, education level, and familiarity with technology. Conclusion: Patients perceive both opportunities and risks associated with new nursing technologies. While these tools can enhance care delivery, their success depends on thoughtful implementation that prioritizes human-centered care. Further research is needed to refine these technologies and address patient concerns to maximize their benefits and mitigate unintended consequences.